Agrophysical aspects of technological load regulation on soil cover in the modern agrolandscapes - Barvinskyi, A. (Land Management, Cadastre and Land Monitoring, 2017)
Modern agricultural landuseof researched Tetiivskyi-Boguslavskyi nature-agricultural district of Kyiv region is characterized by high technological loading on the soil covering, associated with the transformation of lands structure and sowing areas of crops under the influence of market situations. The high level of technological loading on land resources causes the development of degradation processes, and as a result – reduced lands productivity. The main reasons are: unbalanced development of the productive forces and exhausting exploitation of land resources, producers ignoring of environmental imperatives, technical, technological and organizational backwardness of agricultural production; embryonic nature of ecological and economical mechanism of land use and realization of land protection measures, the lack of perfect legal framework of regulating and management of resource- ecological security at national, regional and local levels. Increasing of anthropogeneous pressure on soil (excessive soil tillage in agricultural landscapes, ecologically unsustainable use of agricultural chemicals, high intensity of heavy agricultural machinery, etc.) leads to increase of degradation processes almost on the all area of arable land (Medvedev, 1994). So important is the continuous monitoring of agrophysical condition of soils and development of scientific and practical foundations of optimizing the physical parameters of fertility. The environmentally unbalanced application of anthropogeneous factors results in agrophysical degradation of arable lands, what is displaied in top soil overcompaction.Experimentally found that depending on how the agricultural land use equilibrium bulk density of the gray forest soils varies between 1,35-1,58 g/cm3, dark-gray forest soils - 1,36-1,44, podzolized chernozem - 1,26-1,33, typical chernozem- 1,09-1,18 g/cm3, that indicating the imbalance of soil-physical factors, a significant deviation from the requirements of crops and could lead eventually to lower soil fertility on 50-60 % (Bondarev, 1989). To reduce the load process should be at soil-climatic zones and the landscape in general - to optimize the lands structure and sowing areas through technological distribution of arable land with regard to their suitability for growing of majorcropsgroups; at a particular catchment (slope) -to makeenvironmental assessment of certain technologicaloperations and technologies ofcrops growing in general; ensure environmental sustainability improvement of soil by increasing organic matter content and saturation of soil absorbing complex by calcium, and reducing mechanical stress on the soil of agricultural machinery by introducing the principles of conservative farming. According to experimental data obtained in the long stationary experiment, created in Kyiv agrosoil area, improve the environmental sustainability of light loamy gray forest soils requires an integrated systems approach with a view to the simultaneous optimization of both agro-chemical and physical properties. The combination of fertilization and liming, contributing to the saturation of the soil absorbing complex of calcium and magnesium to 70-73%, increase humus content to 1,6-1,7%, the growth factor structuring of 1,35 to 1,49, indicating increased the potentialability of the soil to the formation of microstructure. Thus, the studied soil bulk density decreased from 1,48 to 1,42 g/cm3, and water permeability increased from 48,9 to 60,7 mm/h. However, regression analysis of the data shows that optimizing the equilibrium bulk density of light loamy soils should increase the humus content to 2,2-2,4%, as improved physical-chemical and agrochemical properties of topsoil without substantial transformation of organic matter content is not leads to significant and sustainable changes in their physical properties. Key words:technological load, agrophysicaldegradation, ecological stability of soil, structure of crops areas, agricultural land use.